Challenges of Soil Taxonomy and WRB in classifying soils: some examples from Iranian soils - Salehi, Moahammad Hassan (Bulletin of Geography. Physical Geography Series, 2018)
The two most widely used soil classification are Soil Taxonomy (ST) and World Reference Base for Soil Resources (WRB). The purpose of this paper is to clarify the differences and the similarities between ST and WRB in their current state, with some examples for representative soils in arid and semi-arid regions of Iran. Four representative pedons were classified and soil units from WRB were compared to those obtained by using ST at the family level. WRB could show the status of polluted soils by heavy metals through “toxic” qualifier and its subqualifiers. On the other hand, ST could indicate the status of shallow soils in our studied soils but it was not able to show gleyic conditions and the existence of salic horizon because of the differences of salic horizon criteria with WRB. Special effort should be done to quantify various anthropogenic activities in upcoming editions of both classification systems.